A Mindfulness Program Manual for People With Dementia. (November 2017) - Chan, Joanne; Churcher Clarke, Anna; Royan, Lindsay; Stott, Joshua; Spector, Aimee
This article describes a 10-session group-based Mindfulness Program for people with mild to moderate dementia. It aims to equip people with dementia with skills to manage psychological distress, with support from carers. The Mindfulness Program was developed through reviews of existing literature, consultation with experts, and a focus group with people with dementia. In a randomized controlled feasibility and pilot trial with people with mild to moderate dementia in care homes, it was found to significantly increase quality of life. The manual presented here is designed to be administered flexibly to promote participants' personhood. The protocol is designed for use by therapists with experience in practicing mindfulness meditation.